Pengaruh Social Media Marketing terhadap Keputusan Pembelian Konsumen pada Kentucky Fried Chicken (KFC) Cabang Transmart Jember - Ainun Ajizah; Achmad Hasan Hafidzi; Tiatit Diansari Reskiputri (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study intends to examine and learn more about how social media marketing is used and how it affects consumer purchasing decisions at the Kentucky Fried Chicken (KFC) Jember Transmart location. Researchers use characteristics including community building, linking, and content creation. The research method used in this study is quantitative research. In the meanwhile, researchers employ questionnaires, observations, interviews, and papers as study tools to gather the required data. The participants in this study are KFC Transmart Jember customers. 385 persons in total responded to the survey. Then, researchers use purposive sampling as a sample technique. Multiple linear regression analyses were performed on the already-gathered and acquired data. The study’s final findings demonstrate that the four factors: content creation, sharing, connecting, and community building have a positive and significant impact on consumer choices when they are making food and beverage purchases at KFC Transmart Jember. Keywords: KFC, Purchase Decision, Social Media Marketing